Body side and predominant motor features at the onset of Parkinson's disease are linked to motor and nonmotor progression. Issue 2 (16th September 2013) - Baumann, Christian R.; Held, Ulrike; Valko, Philipp O.; Wienecke, Miriam; Waldvogel, Daniel
ABSTRACT Patients with Parkinson's disease most often have asymmetric motor features at onset, and specific motor signs (ie, tremor versus bradykinesia and rigidity) frequently characterize the first few years of disease evolution. Some previous clinical evidence has suggested that body side and a predominance of motor manifestations at disease onset are linked to long‐term evolution and disease progression. We prospectively analyzed 206 patients with Parkinson's disease according to the most affected side and predominant motor signs at onset. Patients were divided into left‐side rigid‐akinetic (n = 71), right‐side rigid‐akinetic (n = 59), left‐side tremor (n = 41), and right‐side tremor (n = 35) subgroups. These subgroups were compared in terms of motor and cognitive functions, mean motor deterioration per year (calculated as the motor score divided by disease duration), total equivalent doses of dopaminergic drugs, and the presence of hallucinations and rapid eye movement sleep behavior disorder. Disease duration was similar in all groups. Motor fluctuations were more likely to occur in rigid‐akinetic patients. In a multiple model analysis adjusted for potential confounders, faster disease progression was associated with right‐side (P = 0.045) and rigid‐akinetic onset (P = 0.001). With respect to nonmotor symptoms, the rigid‐akinetic type was associated with increased risk of cognitive decline (P = 0.004) compared with the tremor type. A trend was noticed toward an increased risk of developing visual hallucinations in rigid‐akinetic patients and toward an increased frequency of rapid eye movement sleep behavior disorder in those who had left‐sided onset of symptoms. Our findings corroborate that body side and type of motor signs at the time of diagnosis affect the evolution of motor severity and may also have an impact on some nonmotor manifestations. © 2013 Movement Disorder Society